Illustrated catalog of the types of Staphylinidae (Insecta: Coleoptera) deposited in the Museu de Zoologia da Universidade de São Paulo, Brazil - Caron, Edilson; Buss, Bruna Caroline; Zilberman, Bruno; Bortoluzzi, Sidnei (Zootaxa, 2025)
The Museu de Zoologia da Universidade de São Paulo (MZUSP) houses one of the most extensive collections of zoology in Latin America. Its type collection of Staphylinidae includes items identified by nearly 30 entomologists, such as Charles Seevers, Erich Wasmann, Lubomir Hromádka, Max Bernhauer, Otto Scheerpeltz, and Thomas Borgmeier. This catalog details every type specimen of Staphylinidae housed at MZUSP. The collection spans more than 2,300 type specimens, including secondary types, from nearly 200 species and eight subfamilies. About 70% of the species are primary types, with 77% originating from Brazil. Thomas Borgmeier is the most represented taxonomist, accounting for 34% of the species with types at MZUSP, followed by Max Bernhauer and Charles Seevers. We offer details on the labels and photos of the dorsal aspect of all types, and the labels of at least one specimen from each species. Furthermore, we detail specimens labeled as types that have not yet been officially recognized as such.